Supply chain integration and culture under globalization: A systematic review and global research agenda - Amol S. Dhaigude; Debmallya Chatterjee; Giridhar B Kamath (Research in Globalization, 2025)
Cultural peculiarities affect how corporations in global supply chains integrate, but unfortunately, there has been a lack of systematic documentation of this amalgamation. This study explores a complex global-level relationship among supply chain integration (SCI) and culture. This study synthesized current research from premier academic publications (A and A* levels) through text analysis, the SPAR-4 systematic literature review (SLR), and the theory, characteristics, context, and methodology (TCCM) framework to elucidate the intricacies of cross-cultural collaboration. This study proposes 60 research questions spread across the theoretical development, context, characteristics, and methodology to enhance the research on the amalgamation of SCI and culture at a global level. This study also proposes a research framework to guide future research on chaotic global supply networks. This study provides comprehensive knowledge of cross-cultural collaborative dynamics for practitioners and scholars, laying the groundwork for future empirical research and strategic management.